Atuações de pedagogas em um espaço não escolar: um estudo de caso da instituição Liceu de Artes e Ofício Claudio Santoro - Unidade Parintins - Lima, Mariza Viana (Brasil, 2024)
This research aimed to analyze what are the practices and actions related to the role of pedagogues and other members of the pedagogical sector of the Lyceum of Arts and Crafts Claudio Santoro - Parintins Unit, in the Lower Amazon, an educational, artistic, social and cultural space . For the methodological development, a qualitative approach was proposed, through which it made it possible to unveil and get to know an environment of non-school education. In this thinking, the main questioning of the research was: How are the pedagogical practices in this space, developed by the pedagogical sector, such as: elaboration of menus of the offered courses; lesson plans; formations; training, meetings and other activities, whose pedagogical sector is, become gears for its full development. Future contributions arise from the premise that it is necessary to add the experiences of pedagogues in a non-school space. Thus, identifying the actions and skills in this space allows a broader view of the role of these professionals in non-school spaces. The subsidies exposed here refer to a better panorama of the work of pedagogues and pedagogues, allowing less conventional approaches during training.